Tackling segmentation to advance universal health coverage: analysis of policy architectures of health care in Chile and Uruguay - Pamela Bernales-Baksai (BMC, 2020)
Abstract Background With the turn of the century, most countries in Latin America witnessed an increased concern with universalism and redistribution. In the health sector, this translated into a wide range of reforms to advance Universal Health Coverage (UHC) that, however, have had to cope with health systems that stratified the population since their foundation and the further segmentation inherited by market-oriented policies in the 1980s and 1990s. Studies on social welfare stress the relevance of cross-class alliances between the middle and working classes to reach universal and sustainable social benefits. Consequently, the endurance of separate health schemes across groups of the population in most countries in Latin America may seriously hamper the efforts towards UHC. Aim This article addresses the potential of current policy architectures of health care to tackle segmentation between social classes in access to health services in two of the best performers of health coverage in the region, namely Chile and Uruguay. Methods The article is a comparative case study based on a literature review and applies an analytical framework that links universal outputs to the policy architectures of health care. The study assesses universal outputs in terms of coverage, generosity and financial protection, identifying equity gaps in each of these dimensions across groups of the population. Findings Latest processes of reform for UHC in Chile and Uruguay perform highly regarding population coverage. Nevertheless, equity gaps in access to quality services and financial protection remain. In both countries, such gaps relate to the eligibility criteria. In Chile, segmentation is reinforced by the persistence of separated pools of resources that hinder solidarity. Besides, the significant role of private actors and differences in quality between public and private service providers continue to push middle and upper-middle classes to private options. Uruguay's health reform reinforced the public system and promoted financial solidarity by pooling and progressively allocating resources. Despite this, fragmentation in service provision continues the segmentation of access to health care. Conclusions The study shows differences in the options of reforms for UHC in Chile and Uruguay and the relevance of policy architectures to reverse, or conversely deepen, segmentation across groups of the population.